Formação do léxico da língua portuguesa. - Sousa, Rafaela da Silva Dias (Universidade Federal do Tocantins, 2022)
This paper aims to address the linguistic implications for the formation of the lexicon of the Portuguese language, specifically Brazilian Portuguese. We tried to answer which factors contributed to the change of the Portuguese language. We had as theoretical basis the approaches of TEYSSIER (2007); translated by Celso Cunha, SPINA (2008), ILLARI (1999), among others who also discuss the history of the Portuguese language. The methodology used was based on fragments of texts from different times, we used some excerpts of literary works such as troubadour songs, written in Portuguese Galician; the riverside song and an excerpt from José de Alencar's book Iracema to discuss the influence of indigenous words on the Portuguese lexicon; among other texts to make comparisons between the phases of the language. Based on the analyzed fragments we tried to explain the phonological and morphological alterations of the words. Through studies about the trajectory of the Portuguese language, we found that it is formed not only by words of Latin origin, but by contributions from several languages that were present in the lexicon, among these influences, we highlight: the Arabic, the Germanic, the Celtic, African, Greek, Spanish, French and also foreign, as in the English case, which indirectly influenced.